Utilization of Soybean Oil as An Anti Mosquito Lotion - Sansabhilla, Faradiva; Faiqoh, Elok; Allamah, Labibah; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2020)
The use of repellents as anti-mosquito is currently feared to contain a lot of chemicals so it needs innovation to anticipate them. This study aims to make soybean oil as an innovation in making lotions and to know the manufacturing process. The method of extracting soybean oil is pressing using a Hydraullic Press. Soybean oil extraction based on 9 variables changes namely preheat temperature 100°C; 120°C; 140°C and pressure of Hydraullic Press 1800 psi; 2000 psi; 2200 psi as the test material, the best results were obtained at variable 5 with a variable 120°C and 2000 psi obtained the results of a density of 0,929 gr / ml, viscosity of 28,07 cP and a yield of 3,1%. Making lotion using variable 10 gr of the best soybean oil, Glycerin 20 gr, cetyl alcohol 4 gr, CMC 3 gr, Arabian Gom 0,5 gr and aquadest 10 ml, obtained the results of pH 6 and density 1,0428 gr/ml.